2014
DOI: 10.1111/jopy.12105
|View full text |Cite
|
Sign up to set email alerts
|

Identification During Imposed Change: The Roles of Personal Values, Type of Change, and Anxiety

Abstract: Using a person-situation perspective, we explain what happens to individuals' identification with a collective in the context of a change. We propose that given the anxiety that often emerges during change, individuals' personal values (conservation and openness to change) interact with type of change (imposed vs. voluntary) in predicting identification following change. In a pilot, longitudinal field study (N = 61, 67% female) of an imposed university campus relocation, we measured employees' values and ident… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0
3

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 49 publications
0
14
0
3
Order By: Relevance
“…Several studies have exemplified the positive impact of conservation values on compliance to organisational authorities. Sverdlik and Oreg () found that when organisational change was imposed, emphasising conservation (vs. openness to change) values positively predicted identification with the organisation. In an ongoing research among university faculty members (Elster and Sagiv, ), emphasising conformity values predicted satisfaction with top management and deference identification (i.e., idealisation of the organisational symbols and leadership, see Roccas et al, ), two and four years after the participants reported their values.…”
Section: Value Profile Of Managersmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have exemplified the positive impact of conservation values on compliance to organisational authorities. Sverdlik and Oreg () found that when organisational change was imposed, emphasising conservation (vs. openness to change) values positively predicted identification with the organisation. In an ongoing research among university faculty members (Elster and Sagiv, ), emphasising conformity values predicted satisfaction with top management and deference identification (i.e., idealisation of the organisational symbols and leadership, see Roccas et al, ), two and four years after the participants reported their values.…”
Section: Value Profile Of Managersmentioning
confidence: 99%
“…Several studies have exemplified the positive impact of conservation values on compliance to organisational authorities. Sverdlik and Oreg (2015) found that when organisational change was imposed, emphasising conservation (vs. openness © 2018 International Association of Applied Psychology.…”
Section: Openness To Change Versus Conservation Valuesmentioning
confidence: 99%
“…A series of studies show that openness-to-change values are positively associated with voluntary change while they have a negative relationship to imposed changethe opposite is true for conservation values (Sverdlik & Oreg, 2009, 2015. In another study, Sverdlik and Oreg (2015) studied the relationship between type of change (imposed/voluntary), values, and organizational identification. They found that imposed change has a positive relationship to identification when conservation values are prioritized and a negative relationship when openness-to-change values are prioritized.…”
Section: Previous Research On Change and Valuesmentioning
confidence: 99%
“…An important consideration in relation to the above arguments on the transformative power of conflict deployment is the issue of value fit to life situations (i.e., the interaction of individual values and environment). Bardi and colleagues () found that self‐selection into different life situations was driven by preexisting value configurations, and that the value change that did occur after a transition was driven by the extent of the change in situation/context (see also Sverdlik & Oreg, , on values and person‐situation fit). In other words, people often choose life transitions based on value configurations that will fit the new context, making changes less likely if the new environment is not highly different.…”
Section: Values and Value Changementioning
confidence: 99%